2020
DOI: 10.1021/acs.jnatprod.9b00759
|View full text |Cite
|
Sign up to set email alerts
|

Furofuranone Lignans from Leucophyllum ambiguum

Abstract: Eight furofuranone lignans with an endo,endo relationship between the oxygen atoms, an exo,exo relationship between the aryl groups, and a chair,chair conformation (1−4 and 6−9), in addition to the α-amino acid (3S)-hydroxy-3′,4′-dimethoxy-L-phenylalanine (5), veratric acid (10), and β-sitosterol (11), were isolated from the powdered and defatted airdried aerial parts of Leucophyllum ambiguum. Four of these lignans, ciquitins A−D, 1−4, were isolated for the first time as natural products. The structures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Though coupling constants could not be clearly seen from peak splitting at H-8 and H-8', they could be deduced from splits at H-7 (J = 8.7) and H-7' (J = 8.6), the large coupling constants suggested the relationships between H-7 and H-8, H-7' and H-8' were both trans. [11] H-7 and H-8' were sterically close assumed from their correlation found at NOESY. Thus, its relative configuration which was the same as that of compound 1 was solved by HÀ H coupling constants combined with cross-peaks of NOESY.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…Though coupling constants could not be clearly seen from peak splitting at H-8 and H-8', they could be deduced from splits at H-7 (J = 8.7) and H-7' (J = 8.6), the large coupling constants suggested the relationships between H-7 and H-8, H-7' and H-8' were both trans. [11] H-7 and H-8' were sterically close assumed from their correlation found at NOESY. Thus, its relative configuration which was the same as that of compound 1 was solved by HÀ H coupling constants combined with cross-peaks of NOESY.…”
Section: Resultssupporting
confidence: 51%
“…1 H‐NMR and 13 C‐NMR spectra showed similar data (Table 1) as those of compound 1 , except for the differences at chemical shifts of the butyrolactone [ δ H 4.52 (d, J =8.7, 1H, H‐7), 5.07 (d, J =8.6, 1H, H‐7′), 2.55‐2.61 (m, 1H, H‐8), 3.29‐3.33 (m, 1H, H‐8′), 3.44‐3.54 (m, 2H, H‐9, 9′); δ C 82.5 (C‐7), 81.3 (C‐7′), 53.6 (C‐8, 8′), 60.1 (C‐9), 173.9 (C‐9′)], which suggested that compound 2 was also a dibenzylbutyrolactone lignan but with a different configuration or conformer. Though coupling constants could not be clearly seen from peak splitting at H‐8 and H‐8′, they could be deduced from splits at H‐7 ( J =8.7) and H‐7′ ( J =8.6), the large coupling constants suggested the relationships between H‐7 and H‐8, H‐7′ and H‐8′ were both trans [11] . H‐7 and H‐8′ were sterically close assumed from their correlation found at NOESY.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Phenolic compounds from natural sources have shown anticholinesterase activity in several studies [ 34 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Phenolic compounds whose anticholinesterase activities have been reported are given in the Supplementary Material ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%